Transcriptome-wide identification of WRKY transcription factors and their expression profiles in response to methyl jasmonate in Platycodon grandiflorus. (31st December 2022) - Li, Jing; Yu, Hanwen; Liu, Mengli; Chen, Bowen; Dong, Nan; Chang, Xiangwei; Wang, Jutao; Xing, Shihai; Peng, Huasheng; Zha, Liangping; Gui, Shuangying
ABSTRACT: Platycodon grandiflorus, a perennial flowering plant widely distributed in China and South Korea, is an excellent resource for both food and medicine. The main active compounds of P. grandiflorus are triterpenoid saponins. WRKY transcription factors (TFs) are among the largest gene families in plants and play an important role in regulating plant terpenoid accumulation, physiological metabolism, and stress response. Numerous studies have been reported on other medicinal plants; however, little is known about WRKY genes in P. grandiflorus . In this study, 27 PgWRKYs were identified in the P. grandiflorus transcriptome. Phylogenetic analysis showed that PgWRKY genes were clustered into three main groups and five subgroups. Transcriptome analysis showed that the PgWRKY gene expression patterns in different tissues differed between those in Tongcheng City (Southern Anhui) and Taihe County (Northern Anhui). Gene expression analysis based on RNA sequencing and qRT-PCR analysis showed that most PgWRKY genes were expressed after induction with methyl jasmonate (MeJA). Co-expressing PgWRKY genes with triterpenoid biosynthesis pathway genes revealed four PgWRKY genes that may have functions in triterpenoid biosynthesis. Additionally, functional annotation and protein-protein interaction analysis of PgWRKY proteins were performed to predict their roles in potential regulatory networks. Thus, we systematically analyzed the structure, evolution, and expression patterns of PgWRKY genes to provide an important theoretical basis for further exploring the molecular basis and regulatory mechanism of WRKY TFs in triterpenoid biosynthesis.